Solid solution nitride/carbon nanotube hybrids enhance electrocatalysis of oxygen in zinc-air batteries - He,G; Han,X; Moss,B; Weng,Z; Gadipelli,S; Lai,F; Kafizas,AG; Brett,DJL; Guo,ZX; Wang,H; Parkin,IP (Energy Storage Materials, 2018)
Bi-functional electrocatalysts capable of both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) are highly desirable for a variety of renewable energy storage and conversion technologies. To develop noble metal alternatives for catalysis, non-noble metal compounds have been tremendously pursued but remain non-ideal to issues relating to stability and population of the number of exposed active sites. Inspired by Engel-Brewer valence bond theory, strongly coupled nickel-cobalt-nitride solid-solution/carbon nanotube hybrids were developed by tuning their bifunctionalities from an atomistic scale. The as-synthesized catalysts demonstrate superior catalytic properties to commercial noble-metal based counterparts, i.e. platinum on a carbon support for ORR and iridium oxide for OER, also with much enhanced stability. First-principle calculations and structural analysis show that the optimized structures potentially possess multiple active sites, both bulk-surface response and separated surface charge distribution from optimization of Ni/Co nitrides could contribute to synergistic effects for improved catalytic performances. This study provides not only unique theoretical insights but also a design concept for producing effective bi-functional catalysts with balanced-ORR/OER active sites for this class of transition metal nitride hybrid system and paves the way for exploring other metal nitrides for similar purposes.